2020
DOI: 10.1186/s12891-020-03490-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of injury definitions on measures of injury occurrence in classical music students: a prospective cohort study

Abstract: Background: Multiple definitions are used to investigate injuries in musicians, resulting in a wide range of prevalence rates. The aim of this study is to establish the impact of different injury definitions on the prevalence of injuries and disability in classical music students. Moreover, the practical implications of using different injury definitions are considered. Methods: A prospective cohort study among first-year classical music students was performed using bimonthly questionnaires focusing on injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…This was implied in a previous study, in which different injury definitions in classical music students were compared. In this study, the “all musculoskeletal complaints” definition resulted in a much higher one-year prevalence (96.6%) than the “medical attention” definition (17.2%), indicating that music students do not easily seek help ( Steemers et al, 2020 ). From these findings, it seems that offering support from healthcare practitioners with a focus on prevention may result in earlier detection of possible injuries.…”
Section: Resultsmentioning
confidence: 67%
“…This was implied in a previous study, in which different injury definitions in classical music students were compared. In this study, the “all musculoskeletal complaints” definition resulted in a much higher one-year prevalence (96.6%) than the “medical attention” definition (17.2%), indicating that music students do not easily seek help ( Steemers et al, 2020 ). From these findings, it seems that offering support from healthcare practitioners with a focus on prevention may result in earlier detection of possible injuries.…”
Section: Resultsmentioning
confidence: 67%
“…Furthermore, a team of health professionals can use this information for suitable support and guidance in recovery or optimizing a healthy way of playing music. The influence of injury definitions on outcomes in classical music students was already investigated by our group ( Steemers et al, 2020a ). We found a large discrepancy between the percentage of using an all musculoskeletal complaint definition (96.6%) compared to a medical attention (17.2%) and time-loss definition (13.8%), all used in the same population.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study, with first-year classical music students aiming to investigate whether the way of defining injury in musicians is a factor impacting the prevalence of injury and disability, revealed that the percentages of injury varied according to the definition considered, demonstrating that the way students understand the https://doi.org/10.7322/abcshs.2020227.1679 musculoskeletal disorder and assign meanings to musculoskeletal issues can impact on the detection of potential injury and therefore the ability for timely intervention 36 .…”
Section: Discussionmentioning
confidence: 99%